You are on page 1of 3

# Topic 1.

## 2: Polynomials, quotient and remainder

You should be able to:
 add, subtract, multiply and divide polynomials
 understand the words ‘quotient’ and ‘remainder’ used in dividing polynomials
 use the method of equating coefficients
 use the remainder theorem and the factor theorem.

## 1.2.1 Polynomials, adding, subtracting, multiplying and dividing

Polynomials = sum of all the terms of axn, where n = 0, 1, 2,…..
a = coefficients
n = degree of the polynomial
0 = constant polynomial
1 = linear
3 = cubic
4 = quartic

## Example 1: (Page 6, Q4d)

f(x) = x3 – 2x2 + 5x – 3 and g(x) = x2 – x + 4. Simplify 3f(x) – 2g(x).

## Example 2: (p.6, Q5l)

Evaluate (x2 + 1)(x – 3)(2x2 – x + 1).

## 1.2.2 Polynomial identities

Example 3: (P. 6, Q7h)
Find the values of A and B for the following polynomial.
(Ax + B)(3x2 – 2x – 1) ≡ 6x3 – 7x2 + 1

Example 4:
Given that for all real values of x,
2x3 + 3x2 – 14x – 5 ≡ (Ax + B)(x + 3)(x + 1) + C
Find A, B, and C.

## 1.2.3 Division of a polynomial with a linear or a quadratic polynomial

Example 5:
Factorise x3 + 3x + 14 given that one factor is (x + 2).

Example 6:
Find the quotient and the remainder of x4 – x3 + 5x2 + 4x – 36 ÷ (x2 – x + 9).

Example 7
Ex 2: Dividing a polynomial using a quadratic expression, remainder and factor
theorem

## 1. Factorise the following polynomial with a given factor:

(a) x4 – 5x – 6 with factor (x2 – x – 2)
(b) x4 + x3 – 12x2 + 4x + 16 with factor (x2 + 2x – 8)
(c) 6x3 + 5x2 – 17x – 6 with factor (3x2 + 7x + 2)
(d) 2x3 – x2 – 15x + 18 with factor (x2 + x – 6)

## 2. Using factor theorem solve the following questions:

(a) Determine if any of the following expression is a factor of 6x4 – x3 – 21x2 – 6x + 8:
(i) x – 1
(ii) x + 2
(iii) x – 2
(b) Find a factor for each of the following functions:-
(i) 4x4 - 4x3 – 9x2 + x + 2
(ii) x4 – x3 + 5x2 + 4x – 36
(iii) x3 – 2x2 – 7x + 12

## 3. Given that f(x) = x3 + ax + b. If (x – 1) is a factor of f(x) and the remainder

is – 6 when f(x) is divided by (x + 1), find the values of constants a and b.

## 4. Given that 6x3 + x2 – 29x + d is divisible by both 2x – 1 and x + 3, find the

values of c and d.

## 5. The cubic polynomial 2x3 + 5x2 + ax – 6, where a is a constant, is denoted

by f(x). Given that (x + 2) is a factor of f(x), find the value of a.

## 6. Given that x3 – 3x2 – 4x + 16 ≡ (x – 2)(x + 3)(x – C) + Px + Q

Find the values of C, P and Q.

## 7. For all real values of x, 3x3 + 5x2 – 4x – 3 ≡ (Ax + 2) (x + B)(x – 1) + C. Find

the values of A, B and C.

8. Given that 2x2 + 11x + C ≡ A(x + 1)2 + B(x + 1) + 4 for all real values of x,
find the values of A, B and C.

9. Given that 6x2 – x – 3 ≡ A(2x + 1)(x – 1) + B(1 – x) + C for all real values of
x, find A, B and C.

10. Given that 4x2 – 6x + 9 ≡ A(x – 1)(2x + 1) + B(x – 1) + C for all real values
of x, find A, B and C.
1.3 Remainder theorem, Factor theorem, Solving polynomial
equations
1.3.1 REMAINDER THEOREM
When a polynomial f(x) is divided by x – a, the remainder R is f(a).

Example 8:
Find the remainder for 3x 4 + x2 – 7x + 6 ÷ (x + 3).

## 1.3.2 FACTOR THEOREM

If x – a is a factor of f(x), then f(a) = 0
If f(a) = 0, then x – a is a factor of f(x).

Example 9
Find one of the factors of the following polynomial by factor theorem:
(a) 2x3 – 9x2 + 7x + 6
(b) 2x3 + 3x2 – 8x + 3

Example 10
Given that both (x – 1) and (x – 2) are factors of 2x3 – x2 + ax + b, find the values of
a and b.

## Example 11 Solve the equation 2x3 – 7x2 + 9 = 0

Example 12 Solve the equation 2x3 = 9x2 – 11x + 2, giving your answer
correct to 2 decimal places where necessary.

## Exercise 3: Solving polynomial equations

1. Solve the following equations:
(a) 2x3 = x2 + 5x + 2 (f) x3 + 4 = x (x + 4)
(b) x3 + 16 = 12x 4
(g) x  32 
(c) 2x3 + 5x2 = 2 – x x
(d) 4x3 + 3x2 – 16x = 12 (h) x(x + 3)(x – 1) = x + 8
(e) 2x3 – 11x = 6 – 3x2

## 2. Solve the following equations, giving your answer correct to 2 decimal

places where necessary.
(a) x3 + x2 – 8x + 4 = 0 (d) 2x2 + 7x = x3 + 12
(b) 3x3 = 5x + 2 (e) 3x3 + 5x2 = 3x + 2
3 2
(c) 8x + 6 = x + x (f) 2x3 + 6x – 6 = (13x – 6)(x – 1)

## 3. Given that P(x) = x4 + ax3 – x2 + bx – 12 has factors x – 2 and x + 1, solve

the equation P(x) = 0.

4. Given f(x) = 2x3 + ax2 – 7a2x – 6a3, determine whether or not x – a and x + a
are factors of f(x). Hence find, in terms of a, the roots of f(x) = 0.